Antibiotic multidrug resistance in the cystic fibrosis airway microbiome is associated with decreased diversity. Issue 9 (September 2018) - Hahn, Andrea; Burrell, Aszia; Fanous, Hani; Chaney, Hollis; Sami, Iman; Perez, Geovanny F.; Koumbourlis, Anastassios C.; Freishtat, Robert J.; Crandall, Keith A.
Abstract: Background: Cystic fibrosis (CF) is associated with significant morbidity and early mortality due to recurrent acute and chronic lung infections. The chronic use of multiple antibiotics increases the possibility of multidrug resistance (MDR). Antibiotic susceptibility determined by culture-based techniques may not fully represent the resistance profile. The study objective was to detect additional antibiotic resistance using molecular methods and relate the presence of MDR to airway microbiome diversity and pulmonary function. Methods: Bacterial DNA was extracted from sputum samples and amplified for the V4 region of the 16S rRNA gene. An qPCR array was used to detect antibiotic resistance genes. Clinical culture results and pulmonary function were also noted for each encounter. Results: Six study participants contributed samples from 19 encounters. Those samples with MDR (n = 7) had significantly lower diversity measured by inverse Simpson's index than those without (n = 12) (2.193 ± 0.427 vs 6.023 ± 1.564, p = 0.035). Differential abundance showed that samples with MDR had more Streptococcus (p = 0.002) and Alcaligenaceae_unclassified (p = 0.002). Pulmonary function was also decreased when MDR was present (FEV1, 51 ± 22.9 vs 77 ± 26.7, p = 0.054; FVC, 64.5 ± 22.7 vs 91.6 ± 27.7, p = 0.047). Conclusions: The presence of MDR within the CF airway microbiome was associated with decreased microbial diversity, the presence of Alcaligenes, and decreased pulmonary function.